Studi Optimasi Produksi Alat Gali Muat dan Alat Angkut Pada Kegiatan Pengupasan Overburden Menggunakan Metode Match Factor Berdasarkan Efisiensi Biaya Operasional Di Pit Eagle 3 PT. Bumi Karya Makmur, Job Site PT. IPC, Bantuas, Kota Samarinda, Provinsi Kalimantan Timur - Joko Handayani; Try Gamela Saldy (Journals Mining Engineering : Bina Tambang, 2022)
Overburden stripping is one of the activities that greatly affects mining activities, the faster the overburden stripping activity, the coal mining activities will be in accordance with the targets set by PT. Prosperous Work Earth. In carrying out the activities of stripping and transporting overburden in pit eagle 3 PT. Bumi Karya Makmur operates Caterpillar Excavator 345 GC, 340 D, and 320 GC units as digging and loading equipment and Dump Truck units for HINO 500 FM 260 JD and IVECO 682. The current problem is not achieving the overburden production target at pit eagle 3 in April 2021 is 125,000 bcm while the actual is 108,980,21 bcm. The method used in this study is the match factor method. Due to the incompatibility of work between digging and loading equipment, it is necessary to optimize tool productivity and work compatibility between loading and unloading equipment and transportation equipment. The actual value of the match factor between the digging and loading equipment is 1.186. To get the match factor value, cycle time optimization is carried out and the reduction in the number of transportation equipment used so that the match factor value becomes 0.986. So the production of loading and unloading equipment is 135.343,894 bcm/month and the means of transportation is 210.633,110 bcm/month. From the calculation results, it is obtained that the operational costs of loading equipment and transportation equipment for overburden removal before being analyzed are Rp. 469.266.180,92 or Rp. 4.247,04 /bcm. After analyzing the overburden stripping in accordance with the planned production target, the costs incurred are Rp 492.437.946,74 or Rp. 3.638,42 /bcm.